Controlled release in oral drug delivery - Wilson, Clive G.; Crowley, Patrick J. (Springer eBooks., 2011)
Controlling the rate, extent and time of a drug's delivery can optimize its performance in many ways, relative to "immediate release" delivery. Such optimized design requires a broad knowledge base of topics such as gastro intestinal tract physiology, polymer science, and the mechanisms by which drugs are released from the formulated units. Technologies to ?reduce to practice? also need to be carefully considered. Such knowledge must be allied to the physico chemical properties of the drug, its pharmacokinetic behaviors, enzyme susceptibility and other factors that can affect absorption or timecourse in the biosystem.   Traditionally, controlled release systems tended to be ?second-generation products, building on accumulated clinical experience.  However, better awareness of the molecular biology of drug action and the promise of biomarkers and personalized medicine may mean that optimizing performance by controlling release may become a first option in new product development. Such optimization may well help reduce the alarming attrition rates that are now prevalent in new drug development.   Controlled Release in Oral Drug Delivery provides chapters, dealing with all facets of the above subject matter, and its challenges. Authors have been drawn from academia, providers of excipients and from those designing controlled release systems in industrial R&D and manufacture. The contents provide a unique blend of cutting edge knowledge, data on materials and practical experiences.  It is essential text for students, researchers and industrial engineering, formulation and manufacturing technologists as well as quality testing and control functions.   Clive Wilson is the J. P. Todd Professor of Pharmaceutics at Strathclyde University in Glasgow, Scotland and the current president of the European Union Federation for Pharmaceutical Sciences. He is the Chief Scientist of Bio-Images Research Group, a Phase II imaging specialist clinical unit in Glasgow Royal Infirmary. Major areas of research have been the study of the behaviour of drug formulations in man.  With colleagues at Nottingham, he pioneered applications of scintigraphy in the study of physiological and patho-physiological effects of transit on drug absorption and began the investigations into regional drug absorption in man.  This was later applied to the design and optimisation of oral dosage forms, in silico modelling of formulations in man and  studies on IVIVR. He has published more than 150 papers, six books and over 130 reviews and book chapters. He was made a fellow of the Controlled Release Society in June 2010 and a Fellow of the Academy of Pharmaceutical Sciences in September 2010.   Patrick Crowley has over 40 years? experience in dosage form development in the pharmaceutical industry, in both the UK and USA.  He has played key roles in the development of 16 commercial products, including fermentation products, semi synthetics, synthetic structures and a biopharmaceutical product and holds several formulation-related Patents. His interests and publications include drug and product stability, enhancing performance by dosage form design and the application of Quality by Design principles and practices in dosage form development, manufacture and control.